GIS-Based Interactive Technology in Demographic Record Management and Mapping Towards Sustainable Community - Abdullah, Suzanah; Mohd Hussain, Nur Huzeima; Haron, Norhazlan; Abdul Jalil, Safurah; Osoman, Muhammad Ariffin (International Journal of Sustainable Construction Engineering and Technology, 2023)
Management of demographic records plays a vital role in understanding and planning for the needs of community living. However, managing conventional records requires more time, cost, and energy without accurate assurance. As there are raising concerns in assessing community information for charity purposes, safety coordination, and crime prevention, especially during emergencies; integrating demographic data with spatial information is becoming significantly important. This paper aims to establish an accessible and visible digital platform of demographic information for respective sectors, namely, the KRT, Qariah group, NGOs, and representatives of CSR projects. The objective is to digitize interactive demographic record management and mapping through GIS-based technology. This study adopts a Geographical Information System (GIS) to digitize information using web GIS integrating with the Unmanned Aerial Vehicle (UAV) technology for data acquisition in the community sampling areas; Puncak Iskandar. The proposed system which leverages the power of spatial analysis and visualization, utilizes GIS technology to store, analyse, and visualize demographic records in a geographical context. It incorporates various demographic data sources, such as census data, health records, and administrative data in managing more efficient and effective data with lower cost, energy, time, and resources. Furthermore, the GIS-based system enables the identification of spatial disparities, inequalities, and interventions in demographic characteristics. Therefore, the integration of this system into community demographic management has provided a powerful platform for accessing and coordinating population dynamics, problem-solving, and sustainable development. The implementation in Puncak Iskandar enhances the accessibility, and visualization of demographic data, enabling policy-makers, researchers, and planners to make informed decisions based on a geographical perspective. The findings demonstrate the reliability of GIS-based demographic record management in a community living towards supporting evidence-based planning, resource allocation, and policy formulation for a wide range of applications, including urban planning, public health, and social services towards a sustainable future.